COASTAL INLAND COMMUNITY KNOWLEDGE ABOUT ISLAMIC BANKING PRODUCTS (CASE STUDY OF REMBAYAN VILLAGE, WEST KUTAI REGENCY) - Nur Shidik; Darmawati Darmawati; Kokom Komariah (Department of Islamic Banking, Faculty of Islamic Economics and Business (FEBI), State Islamic University of Sultan Aji Muhammad Idris Samarinda, 2026)
The development of Islamic banking in Indonesia shows positive growth, but public literacy and understanding of Islamic banking products remains relatively low, particularly in rural and remote areas. This study aims to analyze the level of public knowledge of Islamic banking products in Rembayan Village, Mook Manaar Bulatn District, West Kutai Regency, and identify influencing factors. The study employed a qualitative descriptive approach, with data collection techniques including in-depth interviews, non-participant observation, and documentation. Nine informants were selected using a purposive sampling technique. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that public knowledge of Islamic banking products is still at the